Income Analysis of the Ke'te Kesu Tourism Attraction in North Toraja Regency - Jumiati Audina Rappan; Widyastuti; Maliki , Rendra Zainal; Saputra , Iwan Alim (LPPM Universitas Tadulako, 2021)
The research aims to find out the revenue of the tourist attraction Ke'te Kesu and to know the impact of COVID-19 on the tourism sector. This research uses purposive sampling, which is the technique of picking up informants with certain considerations who are thought to know the most about what the researcher expects or knows about the object or social situation being studied so that it can facilitate researchers. Primary research data is obtained directly while secondary data is data that comes from an instance that is related to an object that is carefully examined. The method used in this study is qualitative descriptive using documentation and interviews after which the results are analyzed descriptively. Research results show that the increase and decrease in tourist revenue of Ke'te Kesu is influenced by the number of tourists. Visitors from outside the region are more than visitors from abroad, it's the impact of the COVID-19 pandemic that causes out-and-in from an area and/or country that was not as free before the pandemic. In 2018, visitors totaled 47.610 people total income of Rs.21.400,000, in 2019 visitors 63.650 people total revenues of Rs.1.012.650,000, the year 2020 visitors 22.100 people total revenue of Rs.253.500.000, in 2021 visitors 39.600 people total earnings of Rs.535250.00, and in 2022 visitors 45.625 people total incomes of Rs.692125,000. The number of tourists increased but not with the revenues of the merchant because the tourists who visited minimal in doing the sale-buy transactions with the merchants. Nowadays the entrepreneur is eager to promote his trade to attract the interest of the buyer. This provides a benefit to the Ke'te Kesu Foundation to increase the number of visitors because every buyer who will make a sale-buy transaction within the tourist attraction complex must pay for a ticket to enter